1990
DOI: 10.1099/0022-1317-71-2-271
|View full text |Cite
|
Sign up to set email alerts
|

Localization of antigenic sites of the E2 glycoprotein of transmissible gastroenteritis coronavirus

Abstract: Four antigenic sites of the E2 glycoprotein of transmissible gastroenteritis virus were defined by competitive radioimmunoassays ofmonoclonal antibodies (MAbs). Here, we describe the localization of these sites by testing the antigenicity of protein fragments and prokaryotic expression products of E2 gene fragments, and by sequencing of MAb-resistant (mar) mutants. Partial proteolysis of purified E2 protein allowed the isolation of a 28K fragment recognized by both site A-and site C-specific MAbs. An antiserum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 34 publications
1
73
0
1
Order By: Relevance
“…We were not able to confirm our result by using other techniques, because our neutralizing MAbs did not bind to relevant synthetic peptides in a Pepscan analysis (Geysen et al, 1984) or to prokaryotic expression products of S1 gene fragments (Kusters et al, 1989a). This failure is caused by conformation dependence of the antigenic sites Lenstra et al, 1990). The amino acids composing the epitopes of some MAbs are widely separated on the sequence map (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We were not able to confirm our result by using other techniques, because our neutralizing MAbs did not bind to relevant synthetic peptides in a Pepscan analysis (Geysen et al, 1984) or to prokaryotic expression products of S1 gene fragments (Kusters et al, 1989a). This failure is caused by conformation dependence of the antigenic sites Lenstra et al, 1990). The amino acids composing the epitopes of some MAbs are widely separated on the sequence map (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The antigenic structure and location of neutralization epitopes have been reported for two other coronaviruses: transmissible gastroenteritis virus (TGEV) (Correa et al, 1990;Delmas et al, 1990) and mouse hepatitis virus (MHV) (Parker et al, 1989). It is difficult to compare neutralization epitopes of these coronaviruses directly with those of IBV, however, since the sequence identity of IBV S1 and the N-terminal part of S of the other viruses is low (de Groot et al, 1987b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previously characterized TGEV-specific monoclonal antibodies (MAbs; Correa et al, 1988Correa et al, , 1990Jimrnez et al, 1986) were kindly provided by Dr L. Enjuanes (Centro Nacional de Biotecnolog~a, CSIC, Madrid, Spain). The porcir~e Ig class-specific MAbs, anti-lgA, antiIgG 1 and anti-lgG e were kindly provided by Dr C. R. Stokes (Bristol University, Bristol, U.K.).…”
Section: Methodsmentioning
confidence: 99%
“…Conformation-independent determinants have been found on the N-terminal part of transmissible gastroenteritis virus (TGEV) (Delmas et al, 1990;Correa et al, 1990) and the MHV S1 subunits (Routledge et al, 1991), but the MHV and infectious bronchitis virus $2 subunits have also been reported to bear conserved linear determinants recognized by neutralizing MAbs (Luytjes et al, 1989;Talbot et al, 1988;Routledge et al, 1991 ;Kusters et al, 1990). Two of these B cell epitopes have been tested for their immunogenicity and found to protect mice against lethal MHV infection (Talbot et al, 1988;Koolen et al, 1990).…”
mentioning
confidence: 99%